Shear-flexure-axial load interaction in rectangular concrete bridge piers with or without FRP wrapping - Al-Rahmani, Ahmed Hamid Abdulrahman (Kansas State University, 2015)
Recent applications in reinforced concrete columns, including strengthening and extreme loading events, necessitate the development of specialized nonlinear analysis methods to predict the confined interaction domain of axial force, shear, and bending moment in square and slightly rectangular concrete columns. Fiber-reinforced polymer (FRP) materials are commonly used in strengthening applications due to their superior properties such as high strength-to-weight ratio, high energy absorption and excellent corrosion resistance. FRP wrapping of concrete columns is done to enhance the ultimate strength due to the confinement effect, which is normally induced by steel ties. The existence of the two confinement systems changes the nature of the problem. Existing research focused on a single confinement system. Also, very limited research on rectangular sections was found in the literature. In this research, a model to estimate the combined behavior of the two systems in rectangular columns is proposed. The calculation of the effective lateral pressure is based on Lam and Teng model and Mander model for FRP wraps and steel ties, respectively. The proposed model introduces load eccentricity as a parameter that affects the compression zone size, and in turn the level of confinement engagement. Full confinement corresponds to zero eccentricity, while unconfined behavior corresponds to infinite eccentricity. The model then generates curves for eccentricities within these boundaries. The numerical approach developed has then been extended to account for shear interaction using the simplified modified compression field theory adopted by AASHTO LRFD Bridge Design Specifications 2014. Comparisons were then performed against experimental data and Response-2000, an analytical analysis tool based on AASHTO 1999 in order to validate the interaction domain generated. Finally, the developed models were implemented in the confined analysis software “KDOT Column Expert” to add FRP confinement effect and shear interaction.
Keywords: Rectangular concrete columns; Confinement; Shear; Fiber Reinforced Polymer; Civil Engineering (0543)